Four lessons for financial innovation in agrifood systems - Ambler, Kate; Bloem, Jeffrey R.; de Brauw, Alan; Bakhtiar, M. Mehrab; Maruyama, Eduardo (International Food Policy Research Institute, 2025)
Financial systems are modernizing worldwide, with digital apps, online payments, and rapid loan processing increasingly the norm. Yet the digital finance revolution has yet to take hold in the agrifood value chains of low- and middle-income countries (LMICs), where many small farms and firms lack access to sufficient credit. Obstacles include weather and price risks that are difficult to insure, high transaction costs, a lack of collateral among smallholders and informal firms, and seasonal payment streams.